Application of Computational Fluid Dynamics in Assessing the Hemodynamics in Abdominal Aortic Aneurysms - Vijayajothi , Paramasivam; Kanesan , Muthusamy; Mohammed Rafiq , Abdul Kadir (2010)
Clinical applications of computational modelling is a fundamentally new approach in medical treatment planning and development of predictive methods. In case of cardiovascular disease, these methods could enable physicians to predict the risk of rupture and to determine the optimal hemodynamic conditions for an individual patient. Abdominal aortic aneurysm (AAA) is a common clinical problem. We present a computational simulation which can be used in the predictive medicine, especially in the diagnosis and treatment of AAAs. For this purpose, we developed a code that provides an integrated set of tools to model clinically relevant hemodynamic conditions important in predicting risk of rupture of AAAs. The blood flow dynamics was solved according to the incompressible Navier- Stokes equations for Newtonian fluids. The pulsatility of blood flow was considered. The computational application is based on the three-dimensional finite element method. A typical idealised fusiform AAA model was used to study the flow effects, flowinduced wall shear stresses and pressure. These three criterias play an important role in assessing the hemodynamics in AAAs. (Abstract by authors)